IGF2BP2 promotes pancreatic carcinoma progression by enhancing the stability of B3GNT6 mRNA via m6A methylation. (31st July 2022) - Cao, Pei; Wu, Yufan; Sun, Ding; Zhang, Weigang; Qiu, Junyi; Tang, Zuxiong; Xue, Xiaofeng; Qin, Lei
Abstract: Background: Pancreatic carcinoma (PC) is a highly lethal cancer with an increasing mortality rate, its five‐year survival rate is only approximately 4%. N6‐methyladenosine (m6A) modification is the most common posttranscriptional modification of RNA, it could affect tumor formation by regulating m6A modifications in the mRNA of key oncogenes or tumor suppressor genes. However, its role in PC remains unclear. Methods: We combined bioinformatic analysis with in vitro and in vivo experiments to investigate the expression profile of methylation modulators and identify key m6A regulators in the progression of PC. Further study focused on exploring the target genes binding to the regulators through RIP and immunofluorescence staining experiment. Results: TCGA and Gene Expression Omnibus (GEO) analyses revealed an overall increasing trend in the expression of m6A regulators in PC, and consensus clustering analysis of m6A modification showed that the expression of regulators was negatively correlated with the survival rate. LASSO‐Cox regression analysis revealed that IGF2BP2, METTL3, ALKBH5 and KIAA1429 were associated with hazard ratios (HR), but only IGF2BP2 was sufficiently appropriate for the m6A survival prognosis model. The IHC and WB results verified high protein expression of IGF2BP2 in PC, and IGF2BP2 knockdown inhibited the proliferation and migration of PC cells. We predicted and verified B3GNT6 was observably regulated by IGF2BP2 via RIP assays. In addition, IF staining confirmed the co‐expression of IGF2BP2 and B3GNT6. The tumor‐promoting effect of IGF2BP2 and its co‐expression with B3GNT6 were verified in an animal model. Conclusions: Elevated m6A levels promote PC progression. IGF2BP2 is a credible marker and modulates B3GNT6 mRNA stability, indicating that IGF2BP2 is a potential prognostic marker and therapeutic target in PC progression. Abstract : 1. Bioinformatics reveals that m6A regulators are generally elevated in PC. 2. IGF2BP2 enhances the stability of B3GNT6 mRNA via m6A methylation. 3. IGF2BP2 plays a carcinogenic role, promoting tumor formation in vivo.